DAYA ADAPTASI BEBERAPA VARIETAS PADI KETAN (Oryza sativa glutinous L.) TERHADAP TIGA JENIS TANAH - herdian irwansyah (AGRONISMA, 2021)
Glutinous rice (Oryza sativa glutinosa. L) is one of thousands of types of rice. Glutinous rice plants can be distinguished from other types of rice plants from differences in their starch content, where glutinous rice plants have starch with low amylose content and high amylopectin while rice types generally have high amylose and low amylopectin content. is a split plot experimental design where the types of soil as the main plot and varieties as subplots. Soil Type (J) as the main plot consists of three ; mountain land (J1),  ricefield land  (J2) and dry land (J3), while Varieties (V) as sub-plots consist of five; Subang local variety (V1), Putri Pym 20 variety (V2), Wabon variety (V3), Lauma Kt Putri variety (V4), and Lusi variety (V5). From the two treatments, a combination of treatments was obtained and each treatment was repeated three times. The results showed that in general there was no interaction effect between the treatment of soil type and varieties of glutinous rice. The interaction only occurred at leaf area 7 days after planting, number of tillers 28 days after planting, leaf fresh weight 28 days after planting, and number of empty grains. Soil type treatment had a significant effect on plant height and fresh weight at the age of 21 days after planting with soil type (Tanah gunung). Treatment of rice varieties significantly affected height, number of leaves, number of tillers, stem fresh weight, total fresh weight, dry weight of roots, leaves, stems, flower age. and harvest age.